Software interface for micro hydro sensors interfacing - Khoo, Terh Sheng (Universiti Malaysia Sarawak (UNIMAS), 2012)
Software application for micro hydro sensors interfacing is a project that can aid in remote supervision of the micro hydro system. Micro hydro system consists of several parts that are very crucial and need to be monitored so that it can run in optimum perfonnance. Those variables that need to be monitor are temperature, voltage, current, power, and revolution per minute (RPM). This project is divided into two sections, which are sensors interfacing and software application. Software application is the main topic for this project while sensors interfacing are done by my partner. In software application, it main function are to monitor sensors value and also logging the value into database for future reference. Other than that, it also able to generate graph for each variable after there are data in the database. Graph are use to summarize the perfonnance in period of time while monitoring is for several seconds and preventing any damaged to micro hydro if, there are increasing till critical value for the variables. To retrieve data from sensors interfacing circuit, XBee wireless is used. This will allow software application requesting sensors infonnation without needed physical wire. In addition, it is suit to be use in rural area which a physical wire is not suitable. Finally, technician work to monitor micro hydro can just sit at the monitor room and observing sensors infonnation from software interface. This will prevent from going to micro hydro site every time to measure the variable mention above.